THE RELATIONSHIP OF HYPERTENSION, GENETIC AND DEGREE OF SMOKING WITH THE INCIDENCE OF COPD AT HAJI PUBLIC HOSPITAL SURABAYA - Maharani Dyah Pertiwi; Santi Martini; Kurnia Dwi Artanti; Sri Widati (Universitas Airlangga, 2022)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is a limitation of the inflow and outflow of air caused by inflammation of the inhaled toxin. The incidence of COPD continues to increase every year, and is predicted to be the highest cause of death in the next 10 years. This study aimed to analyze risk factors for the history of hypertension, genetic, and smoking degree with COPD in patients at Haji Public Hospital Surabaya 2019. Methods: This type of research used analytic observational research with a case-control research design. The research sample used simple random sampling. Variables used include hypertension history, smoking degree, and genetic. Result: The results of the Chi-Square statistical analysis were male sex at risk with COPD (OR: 14.7; 95% CI: 6.28-34.5); Age> 40 years at risk with COPD (Odds Ratio (OR): 116.8; 95% CI: 15.2-898.4; history of hypertension at risk with COPD (Odds Ratio (OR): 2,512; 95% CI: 1.99-3.16; smoking degree at risk with COPD (high degree OR: 60.95; 95% CI: 7.65-470.3; moderate degree OR: 31.3; 95% CI: 3.85-254.6; low degree OR: 6.1; 95% CI: 1.45-25.6) and smoking behavior (OR: 21.9; 95% CI: 7.71-62.271). Conclusion: It can be concluded that the variables which are risk factors for COPD are male sex, age> 40 years, history of hypertension, smoking behavior and degree of smoking. Recommendations based on the results of this study are expected that the community can be familiarized with a clean and healthy lifestyle so that the incidence of COPD can be reduced.